Growth and yield of bell pepper as influenced by combination of poultry manure and NPK fertilizer - Oluwaseun Anne Hassan; Emmanuel Oluwakayode Ajayi; Lydia Adeola Babatola (Technology in Horticulture)
A field experiment was carried out to assess the growth and yield of bell pepper to different combination ratios of Poultry Manure (PM) and NPK 15:15:15. The experiment was carried out at a research farm of the Department of Agronomy, University of Ibadan, Nigeria. The treatments, consisting of Control (no fertilizer), 100% NPK, 50% NPK + 50% PM, 33% NPK + 67% PM, 67% NPK + 33% PM and 100% PM were laid out in a randomized complete block design (RCBD) with four replications. Five plants from the same treatment were randomly sampled out of 12 plants per bed and tagged for data collection on growth parameters at 3, 4, 5 and 6 weeks after transplanting as well as number of fruits, fruit length and fruit yield. Data collected were subjected to analysis of variance (ANOVA) and significant means separated using Duncan Multiple Range Test (DMRT) at p < 0.05. Results from this study revealed that plants with application of 33% NPK + 67% PM were significantly (p < 0.05) taller and had more leaves and branches than other treatments and control. Likewise, plants which received 33% NPK + 67% PM treatment had significantly higher fruit yield than control and other treatments. It can therefore be concluded that a high level of poultry manure in combination with lower level of NPK (33% NPK + 67% PM) had the best performance in terms of growth and fruit yield of bell pepper and is therefore recommended.